Image Encryption System Based on Joint Transformation Correlation and Ptychography - Yuan Zhong; Linfei Chen; Wenwen Gan; Yuanqian Liu (IEEE Photonics Journal)
In this paper, a new image encryption system based on joint transformation correlation principle and ptycholographic iterative engine is proposed. When the encryption is performed, the original image can be divided into several parts by using the scanning movement of the probe. Each part is encrypted by the joint transformation correlation technology, and the ciphertexts are finally transmitted in the form of many encrypted images. The receiver uses the working principle of the joint transform correlator to decrypt and reconstructs the image by using the ptycholographic iterative engine, which can integrate multiple images with less information into one high-precision decrypted image. Computer simulations prove its possibility.